Diversification over digitalization: a case study on the business survivability strategy of a family business during COVID-19 crisis - Strano, Maria Grazia (Piccola Impresa / Small Business, 2023)
Purpose. The COVID-19 pandemic has led to a situation of generalised economic uncertainty. Many SMEs faced an unexpected crisis, which forced them to review their strategy. These enterprises implemented the best approach to recover and overcome the crisis. Among the different strategies that the companies realized, digitalization and diversification were among the most practised. Although both are risky and expensive, this paper wants to prove that diversifying can be more challenging and carry long-term results. This is due to nowadays attention on digitalization, which is taken for granted and considered an integral part of the business. Despite this, the diversification strategy can play a winning role, evolving the company's portfolio and creating new opportunities. Design/methodology/approach. This is a qualitative case study focused on a small enterprise, which is a family business located in Southern Italy, and its reaction to the crisis through a diversification strategy. Findings. The analysed enterprise initially created a different product, which gave the chance to reduce the loss of revenue and maintain the workforce. Then, the management decided to expand the product network and start a new company. As regards digitalization, it brought unexpected results. Practical and Social implications. The study aims to increase the awareness of SME managers on the possible strategies available for SMEs in critical situations. To do so, company management should evaluate the sector, its competitors, and the availability of resources. Moreover, the case study contributes to the literature on corporate strategies applied during the pandemic period. Originality of the study. Although digitalization has been the most used approach during the pandemic, this paper shows that sometimes even smart intuitions can make a difference in starting a new trade. The correct allocation of budget and resources and a high level of resilience are crucial for success.